2009
DOI: 10.5298/1081-5937-37.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Post Traumatic Stress Disorder—The Neurofeedback Remedy

Abstract: The application of neurofeedback to post traumatic stress disorder (PTSD) in returning veterans is described herein and is illustrated with two case histories. Initially, frequency-based electroencephalogram training was employed to promote functional recovery, in the manner of the traditional sensorimotor rhythm/beta approach. An optimization procedure was employed in which the reinforcement frequency is tailored to the client on the basis of symptom response, with particular regard for the regulation of arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 4 publications
1
45
0
3
Order By: Relevance
“…The positive benefits of neurofeedback as a therapeutic intervention for helping reduce PTSD symptomatology have been reported in a number of studies discussed above (Othmer & Othmer, 2009;Peniston & Kulkosky, 1991;van der Kolk et al 2016). This study specifically identified that artifact corrected neurofeedback, which works by filtering out the contamination that continually results from naturally occurring EMG artifacts such as eye blinks, eye movements and facial activity, significantly improved both auditory and visual attention as measured by the IVA-2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The positive benefits of neurofeedback as a therapeutic intervention for helping reduce PTSD symptomatology have been reported in a number of studies discussed above (Othmer & Othmer, 2009;Peniston & Kulkosky, 1991;van der Kolk et al 2016). This study specifically identified that artifact corrected neurofeedback, which works by filtering out the contamination that continually results from naturally occurring EMG artifacts such as eye blinks, eye movements and facial activity, significantly improved both auditory and visual attention as measured by the IVA-2.…”
Section: Discussionmentioning
confidence: 99%
“…Neurofeedback can be conceptualized as utilizing the brain's inherent capability of neuroplasticity that allows individuals to become aware of the faint cues of their EEG neural activity. By attending to the feedback provided, individuals learn to control and direct their brain activity in order to cultivate a more harmonious and balanced mental state (Budzynski, 1999;Demos, 2005;Nunez, 1981;Othmer & Othmer, 2009;Speckmann & Elger, 1987;White & Richards, 2009). The changes resulting from neurofeedback have been found to result in long-term changes and positive outcomes (Budzynski, 1999;Demos, 2005;Othmer & Othmer, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second was a case series on combat-related PTSD (Othmer & Othmer, 2009). The third was a case series on pediatric epilepsy (Legarda, McMahon, Othmer, & Othmer, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Special significance is also acquired by the application of biofeedback with reference to the persons with posttraumatic stress disorder -PTSD [13]. Nowadays the EEG Biofeedback method is vastly applied in working with attention-deficient children, including those with motor hyperexcitability syndrome with attention deficit (ADHD -attention deficit hyperactivity disorder) [14,15,16,17].…”
Section: Discussionmentioning
confidence: 99%